Educação para a sustentabilidade : contribuição do Instituto Federal de Alagoas para a conservação do rio São Francisco - Silva, Andrea Luciana de Aragão Ribeiro (2018)
As others natural resources, the São Francisco river is evidencing impacts caused by the anthropic actions, mainly because the deforestation of the ciliary vegetation, the discharge of sewage and the reduction of its flow, among others. Those factors interfere in the life of the aquatic species and of the riverside population. The Lower São Francisco is the subregion of this river basin, which more reflects the degradation situation, requiring urgent and specific care, before its capacity for resilience is compromised. The sensitization of communities is suggested as an alternative for the conservation of this water resource, in which education plays an important role in river conservation, and it can be achieved through the adoption of educational actions with a sustainable bias. Thus, this research aims to analyze the contributions of educational actions and the environmental perception of the school community in the Penedo and Piranhas Campuses of the Instituto Federal de Alagoas (“Federal Institute of Alagoas” in English) – IFAL, focusing on the conservation of the São Francisco river. It was used the comparative case-based method, conducted in an exploratory and descriptive way with a mix of qualitative and quantitative approach, based on an interdisciplinary perspective. Data collection was done through documental analysis and semi-structured interviews applied directly to the school community and it was analyzed using the Discourse Analysis of the Subject method, through DSCsoft software. The research results point out that the educational actions promoted by campuses, whether research or extension, or through campainhas and the like, are not very effective in trying to sensitize the school community to the conservation of the São Francisco river, and, therefore, they are also not very effective for the promotion of change of attitude of the individuals that maintain relations of interdependence with the river.